(untitled) (Medical Forum Monthly, 2024)
Objective: The main objective of this study was to determine the prevalence of risk factors in patients presenting with unstable angina, presented at DUHS and BBSUL. Study Design: Observational / cross-sectional study. Place and Duration of Study: This study was conducted at the General Medicine and Cardiology Department of DUHS from March 2016 to March 2017. Materials and Methods: 81 patients with unstable angina in General Medicine and Cardiology ward that fulfilled the inclusion and exclusion criteria and gave informed consent were enrolled for the study. Patients were evaluated for obesity, diabetes, hypertension and dyslipidemia. Results: Total 81 patients with unstable angina were included in this study Out of them 43 (53.1%) were male and 38 (46.9%) were female. Mean age was 60.23 ± 8.7. Majority of patients (49.4%) were lying in 51 to 60 years age group. Raised blood sugar in 51(63%) patients, raised blood pressure in 46(56.8%) & low HDL in 43(53.1%) were more prevalent with other risk factors. Conclusion: This study provides a quantitative estimate of the prevalence of risk factors like Diabetes, low HDL, hypertension, hypertriglyceridaemia and obesity strongly correlates with unstable angina